Media Zoom as an Active Debate Method to Improve Learning Activities in Anthropology Courses at Elementary School Teacher Education Study Program - Zulkifli Amin; Irfan Dahnial (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2022)
The purpose of this research is to see how far students like using zoom media in learning that uses an active debate approach in anthropology courses. This research begins by looking at the phenomenon that the corona virus was first discovered when someone in the city of Wuhan, China was infected. The disease is caused by the SARSCoV2 virus which was previously thought to have symptoms like the common cold, until the WHO declared a COVID-19 pandemic. As of May 26, 2020, the entire country had 5,06,282 cases, including 3,562 deaths. This study uses mixed methods as one of them is to use a literature review in order to be one of the reinforcements for the data in this study, with the analysis followed by a qualitative description. The results of this study can be seen that every student participant likes to use zoom media in carrying out learning, but there are several obstacles faced by students because they are constrained by network barriers that exist in each area, for students who do not experience obstacles for them this is a mistake. one advantage in carrying out learning activities. In addition, the obstacle experienced by lecturers is the lack of active process of students in dialogue and interacting in the online learning process using zoom in the active debate method. For students who do not experience obstacles , this is one of the advantages in carrying out learning activities. In addition, the obstacle experienced by lecturers is the lack of active process of students in dialogue and interacting in the online learning process using zoom in the active debate method. For students who do not experience obstacles , this is one of the advantages in carrying out learning activities. In addition, the obstacle experienced by lecturers is the lack of active process of students in dialogue and interacting in the online learning process using zoom in the active debate method.